Cellular Materials: editorial - Duarte, Isabel (2022)
A growing research effort to develop bioinspired cellular materials for use in commercial, biomedical, engineering and military applications has contributed to emergence of many lightweight and multifunctional metamaterials in recent years. The use of engineered 3D cellular architecture contributes not only to weight reduction and material savings of the components but also their unique mechanical and thermal behaviour, often resulting in their multiple functionalities. Composite and nanocomposite foams, 3D-printed cellular materials, auxetic metamaterials and hybrid foams and structures (e.g. filled hollow structures, sandwich panels, metal-polymer hybrid cellular structure) are some of these examples. The emergence of new bioinspired materials and structures is increasingly gaining importance in the industry. With further production technology development, we are bound to witness ever increasing interest for their application in many industrial products. The papers in this special issue provide representative insight into the recent developments in this field covering the experimental, numerical and theoretical approaches.